Metal-organic frameworks for the sorption of acetone and isopropanol in exhaled breath of diabetics prior to quantitation by gas chromatography - Yu, Li-Qing; Su, Fei-Hong; Ma, Meng-Yuan; Lv, Yun-Kai (Mikrochimica acta (1966), 2019)
A method is described for non-invasive glucose monitoring of diabetics by means of breath analysis. The metal-organic frameworks (MOFs) ZIF-7, UiO-66 and MOF-5 were chosen as sorbents in packed tubes for sampling and preconcentration of acetone and isopropanol which are established diabetes biomarkers. The MOF UiO-66 was found to be the most appropriate sorbent. Following thermal desorption, acetone and isopropanol where quantified by GC. The method has low limits of detection (0.79–0.84 μg·L −1 ) and wide linear ranges (5–2000 μg·L −1 ). It is assumed that the good performance of UiO-66 as a sorbent results from its large surface area and unique porous structure, and from van der Waals interactions. The relative standard deviation for six replicate cycles of sampling and preconcentration using one 50 mg UiO-66 packed tube ranged between 2.3 and 6.7% for intra-day assays, and from 2.7 to 4.3% for inter-day assays. A tube packed with 50 mg of UiO-66 packed tube can be used in over 120 cycles of adsorption/desorption without significant loss of collection efficiency. The GC method has been applied for the analysis of diabetic breath samples, and the recoveries from spiked samples ranged from 89.1 to 107.6%. Graphical abstract Schematic presentation of metal-organic frameworks as sorbents combined with thermal desorption-gas chromatography for the determination of acetone and isopropanol in exhaled breath of diabetics.